2023
DOI: 10.1126/sciadv.ade6066
|View full text |Cite
|
Sign up to set email alerts
|

Extremely low thermal conductivity and high electrical conductivity of sustainable carbon­ceramic electrospun nonwoven materials

Abstract: Materials with an extremely low thermal and high electrical conductivity that are easy to process, foldable, and nonflammable are required for sustainable applications, notably in energy converters, miniaturized electronics, and high-temperature fuel cells. Given the inherent correlation between high thermal and high electrical conductivity, innovative design concepts that decouple phonon and electron transport are necessary. We achieved this unique combination of thermal conductivity 19.8 ± 7.8 mW/m/K (cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Notably, Raman spectroscopy (Figure j) revealed two prominent peaks at 1350 and 1590 cm –1 , expressly correlating to the D and G bands of carbon. In addition, the corresponding mapping image (Figure k), which illustrated the distribution of the degree of graphitization ( I G / I D ), further demonstrated the presence of free carbon in the a-SiC MAs. , …”
Section: Resultsmentioning
confidence: 86%
“…Notably, Raman spectroscopy (Figure j) revealed two prominent peaks at 1350 and 1590 cm –1 , expressly correlating to the D and G bands of carbon. In addition, the corresponding mapping image (Figure k), which illustrated the distribution of the degree of graphitization ( I G / I D ), further demonstrated the presence of free carbon in the a-SiC MAs. , …”
Section: Resultsmentioning
confidence: 86%
“…As shown in Figure 5c, the thermal conductivity of the bilayer CPRCs, including the red, green, and blue coolers, is higher than that of the PVC matrix (0.0134 W m −1 K −1 ) and even higher than the thermal conductivity of air (0.026 W m −1 K −1 ). 63 This enhancement in thermal conductivity can be attributed to the presence of BN nanoplates, which possess high thermal conductivity properties. It is demonstrated that both thermal conductivity and thermal diffusivity increase with a higher content of BN nanoplates (Figure S17), indicating that the incorporation of BN nanoplates into the composite material improves its heat conduction and transfer capabilities.…”
Section: Practical Radiative Cooling Performance Of the Bilayer Cprcsmentioning
confidence: 99%
“…Going beyond polymer fibers, An et al synthesized an anisotropic thermal insulation material based on a layered network of ceramic fibers . Further, Liao et al demonstrated carbon–ceramic fibers with a moderate anisotropy yet an unusual combination of electric transport and thermal insulation …”
Section: Introductionmentioning
confidence: 99%
“…17 Further, Liao et al demonstrated carbon−ceramic fibers with a moderate anisotropy yet an unusual combination of electric transport and thermal insulation. 18 Instead of building blocks with inherent anisotropy, anisotropic material properties can also be generated by a targeted arrangement or nanostructuring. One example is an insulating material fabricated via directional freeze-casting.…”
Section: ■ Introductionmentioning
confidence: 99%